Coated article and method for producing same

By providing a vinyl-based polymer primer layer, a silicone hard coating layer and a light-modified layer on the polycarbonate resin substrate, the problem of insufficient abrasion resistance and weather resistance at high temperatures is solved, and performance comparable to that of glass is achieved.

CN119855704APending Publication Date: 2025-04-18SHIN ETSU CHEMICAL CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380054890.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve abrasion resistance, heat resistance and weather resistance that are comparable to glass on polycarbonate resin substrates at the same time, especially when cracks and peeling are easily generated at high temperatures.

Method used

A primer layer containing a vinyl-based (co)polymer is provided on the resin substrate, and a silicone-based hard coating layer and a light-modified layer are combined with a vinyl-based polymer containing an alkoxy silyl group. The hard coating layer contains an organic silicon resin, colloidal silica and an ultraviolet absorber, and a light-modified layer is formed by light irradiation.

Benefits of technology

The polycarbonate resin substrate has achieved abrasion resistance, heat resistance and weather resistance comparable to glass, and does not require special operation and post-treatment, and is suitable for resin substrates of various shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005249373850000011
    Figure FDA0005249373850000011
  • Figure GDA0005317747610000031
    Figure GDA0005317747610000031
  • Figure GDA0005317747610000101
    Figure GDA0005317747610000101
Patent Text Reader

Abstract

Provided is a coated article having a resin base material, a primer layer provided on the resin base material, a hard coat layer provided on the primer layer, and a light-modified layer formed on a surface layer portion of the hard coat layer, the primer layer is a cured coating film of a primer composition containing (A) a vinyl (co) polymer and (B) inorganic particles having a predetermined median diameter, the (A) vinyl (co) polymer contains (A-1) a vinyl (co) polymer having an alkoxysilyl group, and the primer layer has a film thickness of 1-20 [mu] m. The hard coating layer is a cured film of an organosilicon composition containing (a) an organosilicon resin, (b) colloidal silica, and (c) an ultraviolet light absorber, and the film thickness of the hard coating layer is 1-15 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coated article and a method for producing the same, and more particularly to a coated article having an organic resin substrate such as plastic, a primer layer provided on the substrate, a hard coating layer provided on the primer layer, and a light-modifying layer formed on the surface of the hard coating layer and a method for producing the same. Background Art

[0002] In recent years, as a substitute for transparent plate glass, non-shatterproof or transparent materials with greater shatter resistance than glass have been widely used. For example, plastic substrates, especially polycarbonate resins, have excellent transparency, impact resistance, heat resistance, etc., and are currently used as structural members to replace glass for various purposes such as windows and instrument covers of buildings, vehicles, etc.

[0003] However, since polycarbonate resin molded products are inferior in surface properties such as scratch resistance and weather resistance to glass, there is a strong demand for improving the surface properties of polycarbonate resin molded products.

[0004] As a means of imparting a scratch resistance equivalent to that of glass to the surface of a resin molded product, Patent Document 1 proposes the following method: a protective film produced by a siloxane-based hard coating paint is provided, and then the surface of the protective film is modified by vacuum ultraviolet light to form a light-modified film. On the other hand, if the resin molded product is placed at high temperatures, the light-modified film cannot follow the thermal expansion of the resin and is prone to cracking, which poses problems in terms of heat resistance and weather resistance.

[0005] In Patent Documents 2 and 3, the following method is proposed: a grid mask is placed on a siloxane-based hard coating layer, light is irradiated from the upper part of the grid mask, and light is irradiated to the hard coating layer from the opening of the grid mask, and a photomodification layer and a siloxane-based hard coating layer are alternately formed on the surface of a resin substrate in a shape corresponding to the opening shape of the grid mask, thereby utilizing the expansion of the resin substrate to relax the stress on the photomodification layer and improve heat resistance, and a simpler manufacturing method is desired.

[0006] In addition, Patent Document 4 reports that the heat resistance when heated to 80° C. is improved by making the film thickness of the primer layer containing an acrylic polymer 10 μm or more or forming a primer layer containing 20 to 60 parts by mass of silica particles relative to 100 parts by mass of the acrylic polymer, and forming a siloxane-based hard coat layer and a photomodification layer thereon.

[0007] On the other hand, when the primer layer is thickened or a large amount of silica particles are added, cracks are generated during weather resistance tests, which easily causes early peeling and whitening of the coating film, which poses problems in terms of weather resistance. In addition, polycarbonate resins are sometimes required to have heat resistance at a higher temperature of more than 100°C.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 4536824

[0011] Patent Document 2: Japanese Patent No. 6585758

[0012] Patent Document 3: International Publication No. 2020-044705

[0013] Patent Document 4: Japanese Patent Application Publication No. 2016-030392 Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a covered article having scratch resistance comparable to that of glass and having excellent heat resistance and weather resistance.

[0016] Means for solving problems

[0017] The present inventors conducted intensive research to solve the above-mentioned problems and found that a coated article having a prescribed primer layer containing a vinyl (co)polymer containing an alkoxysilyl group in its molecular structure on a resin substrate, a prescribed siloxane hard coating layer provided on the primer layer, and a photomodification layer formed on the surface portion of the hard coating layer has both scratch resistance comparable to that of glass and excellent heat resistance and weather resistance, thereby completing the present invention.

[0018] That is, the present invention provides:

[0019] 1. A coated article, comprising a resin substrate, a primer layer provided on the resin substrate, a hard coating layer provided on the primer layer, and a light-modified layer formed on the surface of the hard coating layer, wherein the primer layer is a cured film of a primer composition comprising (A) 100 parts by mass of a vinyl (co)polymer and (B) 1 to 19 parts by mass of inorganic particles having a median diameter of 1 to 100 nm as measured by a dynamic light scattering method, wherein the (A) vinyl (co)polymer comprises (A-1) a vinyl (co)polymer having an alkoxysilyl group, the primer layer has a thickness of 1 to 20 μm, the hard coating layer is a cured film of a silicone composition comprising (a) a silicone resin obtained by (co)hydrolyzing and condensing at least one of an alkoxysilane represented by the following formula (1) and a (partial) hydrolysis-condensation product thereof, (b) colloidal silica, and (c) an ultraviolet absorber, and the hard coating layer has a thickness of 1 to 15 μm;

[0020] R 1 mSi(OR 2 ) 4-m (1)

[0021] (Where R 1 Each independently represents a hydrogen atom, or a substituted or unsubstituted monovalent hydrocarbon group, and multiple R 1 can be bonded to each other to form a linking group, R 2 Each is independently an alkyl group having 1 to 3 carbon atoms, and m is 0, 1 or 2.

[0022] 2. The coated article according to 1, wherein the light-modifying layer comprises silicon dioxide;

[0023] 3. The coated article according to 1 or 2, wherein the (c) ultraviolet absorber comprises a reactive ultraviolet absorber represented by the following general formula (2) and a (partial) hydrolysis condensate thereof,

[0024] [Chemistry 1]

[0025]

[0026] [Where R 3 are each independently a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 5 carbon atoms, or a group represented by the following general formula (3), R 3 At least one of them is a group represented by the following general formula (3).

[0027] *-O-(CH2) j -SiR 4 k (OR 5 ) 3-k (3)

[0028] (Where R 4 and R 5 Each is independently an alkyl group having 1 to 5 carbon atoms, j is an integer of 1 to 8, and k is an integer of 0 to 2. The asterisk * indicates a bond to an adjacent atom. )]

[0029] 4. The coated article according to any one of 1 to 3, wherein the surface hardness of the hard coating layer measured by nanoindentation method is 0.10 to 0.50 GPa;

[0030] 5. The coated article according to any one of 1 to 4, wherein (B) the inorganic particles include one or more particles selected from the group consisting of silicon dioxide, zinc oxide, titanium oxide, and cerium oxide;

[0031] 6. The coated article according to any one of 1 to 5, wherein the primer composition comprises (A-1) a vinyl copolymer having an alkoxysilyl group and an ultraviolet absorbing group;

[0032] 7. The coated article according to any one of 1 to 6, wherein the primer composition further comprises (C) one or more ultraviolet absorbers selected from triazine derivatives and benzophenone derivatives;

[0033] 8. The coated article according to any one of 1 to 7, wherein the primer composition further comprises (D) a hindered amine light stabilizer;

[0034] 9. The coated article according to any one of 1 to 8, wherein the primer layer has a thickness of 3 to 15 μm, and the hard coating layer has a thickness of 3 to 13 μm;

[0035] 10. A method for producing a coated article according to any one of 1 to 9, comprising the step of irradiating the surface of the hard coating layer with light having a wavelength of 300 nm or less to form a light-modified layer on the surface layer of the hard coating layer.

[0036] Effects of the Invention

[0037] According to the present invention, a coated article having scratch resistance comparable to that of glass and having excellent heat resistance and weather resistance can be provided. In addition, according to the present invention, no special operation or apparatus is required during the photomodification of the hard coating layer, and no special post-treatment is required after the photomodification. Therefore, excellent scratch resistance, heat resistance, and weather resistance can be more easily imparted to resin substrates of various shapes. DETAILED DESCRIPTION

[0038] The present invention will be described in detail below.

[0039] The coated article of the present invention is a coated article comprising a resin substrate, a primer layer provided on the resin substrate, a hard coating layer provided on the primer layer, and a light-modified layer formed on the surface of the hard coating layer, wherein the primer layer is a cured film of a primer composition comprising a vinyl (co)polymer having an alkoxysilyl group, and the hard coating layer is a cured film of a silicone composition comprising (a) a silicone resin, (b) colloidal silica, and (c) an ultraviolet absorber.

[0040] One feature of the coated article of the present invention is that a UV absorber is included in the hard coating layer. By including a UV absorber in the hard coating layer, when the hard coating layer is subjected to light irradiation for light modification as described later, light is prevented from reaching the primer layer, thereby suppressing the deterioration of the abrasion resistance caused by the peeling of the film and the reduction of adhesion.

[0041] In addition, by providing a primer layer containing a vinyl (co)polymer containing an alkoxysilyl group in its molecular structure, the alkoxysilyl group contained in the above primer layer and / or the silanol group generated by its hydrolysis are utilized to impart reactivity with the siloxane in the siloxane-based hard coating layer, and the adhesion between the substrate and the hard coating layer is improved via the primer layer. At the same time, cross-linking is achieved through the alkoxysilyl group and / or the silanol group generated by its hydrolysis, thereby improving heat resistance and exhibiting excellent scratch resistance and weather resistance.

[0042] <Resin base material>

[0043] The resin substrate in the coated article of the present invention is not particularly limited, but various organic resin substrates are preferably used, and specific examples thereof include polycarbonate resins, polystyrene resins, acrylic resins, modified acrylic resins, polyurethane resins, thiourethane resins, polycondensates of halogenated bisphenol A and ethylene glycol, acrylic urethane resins, halogenated aromatic group-containing acrylic resins, sulfur-containing resins, etc. Among these, polycarbonate resins are preferred.

[0044] Furthermore, the surfaces of these resin substrates may be treated, specifically, by chemical conversion treatment, corona discharge treatment, plasma treatment, acid or alkali treatment, etc. In addition, laminates having a surface layer formed of a resin of a different type from that of the substrate body may also be used.

[0045] Specific examples of the laminate include a laminate having an acrylic resin layer or a polyurethane resin layer on the surface of a polycarbonate resin substrate produced by a coextrusion method or a lamination method, and a laminate having an acrylic resin layer on the surface of a polyester resin substrate.

[0046] <Primer layer>

[0047] The primer layer in the coated article of the present invention is composed of a cured film of a primer composition containing the following components (A) and (B).

[0048] (A) Vinyl (co)polymers

[0049] (B) Inorganic particles with a median diameter of 100 nm or less as measured by dynamic light scattering

[0050] [(A) Vinyl (co)polymer]

[0051] (1) (A-1) Vinyl (co)polymer having an alkoxysilyl group

[0052] The vinyl (co)polymer of component (A) includes a vinyl (co)polymer having an alkoxysilyl group (A-1). As the vinyl (co)polymer having an alkoxysilyl group as component (A-1), for example, a vinyl (co)polymer in which an alkoxysilyl group is bonded to the main chain via a Si-C bond can be listed. As such a (co)polymer, a polymer of a vinyl monomer having an alkoxysilyl group bonded via a Si-C bond, or a copolymer of a vinyl monomer having an alkoxysilyl group bonded via a Si-C bond and other vinyl monomers can be listed.

[0053] Among them, any vinyl monomer to which an alkoxysilyl group is bonded via a Si—C bond can be used as long as it contains one vinyl polymerizable functional group and one or more alkoxysilyl groups in one molecule.

[0054] As the vinyl polymerizable functional group, organic groups having 2 to 12 carbon atoms, such as vinyl, vinyloxy, (meth)acryloyloxy, and (α-methyl)styryl, can be listed. As specific examples, vinyl, 5-hexenyl, 9-decenyl, vinyloxymethyl, 3-vinyloxypropyl, (meth)acryloyloxymethyl, 3-(meth)acryloyloxypropyl, 11-(meth)acryloyloxyundecyl, vinylphenyl (styryl), isopropenylphenyl (α-methylstyryl), vinylphenylmethyl (vinylbenzyl), etc. can be listed. Among these, (meth)acryloyloxypropyl is preferred from the perspective of reactivity and ease of acquisition. It should be noted that in the present invention, the so-called (meth)acryloyl group means an acryloyl group and / or a methacryloyl group.

[0055] Examples of the alkoxy group in the alkoxysilyl group include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, etc. Among these, methoxy and ethoxy are preferred from the viewpoint of easy control of hydrolyzability and easy availability.

[0056] Examples of the silicon-bonded substituent other than the alkoxy group include alkyl groups such as methyl, ethyl, n-propyl, n-hexyl, and n-decyl, and aryl groups such as phenyl. Among these, a methyl group is preferred because of its availability.

[0057] Examples of the vinyl monomer to which an alkoxysilyl group is bonded via a Si-C bond include methacryloxymethyltrimethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxyundecyltrimethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyldimethylmethoxysilane, methacryloxypropyltriethoxysilane, acryloxypropyltrimethoxysilane, acryloxypropylmethyldimethoxysilane, acryloxypropyldimethylmethoxysilane, acryloxypropyltriethoxysilane, acryloxymethyltrimethoxysilane, acryloxyundecyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, allyltrimethoxysilane, styryltrimethoxysilane, styrylmethyldimethoxysilane, and styryltriethoxysilane.

[0058] Among these, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyldimethylmethoxysilane, acryloxypropyltrimethoxysilane and acryloxypropylmethyldimethoxysilane are preferred from the viewpoints of availability, handling properties, crosslinking density, reactivity and the like.

[0059] (A) The amount of alkoxysilyl in component is, for example, in the case where alkoxysilyl is trimethoxysilane, preferably 1 to 50% by mass, more preferably 2 to 30% by mass, and further preferably 3 to 15% by mass relative to the entire (A) component. If it is more than 1% by mass, the crosslinking between the above-mentioned vinyl (co)polymers and with inorganic fillers etc. will fully form a siloxane network, the linear expansion coefficient of the film is reduced, and heat resistance and durability are further improved. And then, by reacting with the siloxane in the hard coat, the adhesion and weather resistance of the hard coat are further improved. In addition, if the amount of alkoxysilyl in component (A) is less than 50% by mass, the crosslinking density is not excessively increased, and the reduction of adhesiveness caused by the superfluous hardness can be suppressed, and the generation of film cracks caused by crosslinking after unreacted alkoxysilyl for a long time is suppressed.

[0060] As other vinyl monomers copolymerizable with the vinyl monomer to which the above-mentioned alkoxysilyl group is bonded via a Si-C bond, there are no particular restrictions as long as they are copolymerizable vinyl monomers, and examples thereof include (meth)acrylic monomers, (meth)acrylates, (meth)acrylonitrile, (meth)acrylamide, alkyl vinyl ethers, alkyl vinyl esters, styrene, and derivatives thereof.

[0061] Specific examples of (meth)acrylates and derivatives thereof include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-heptyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, (Meth)acrylate esters of monohydric alcohols such as n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, lauryl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and benzyl (meth)acrylate;

[0062] (Meth)acrylates of alkoxy (poly)alkylene glycols such as 2-methoxyethyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate (the number of ethylene glycol units is preferably, for example, 2 to 20), and methoxypolypropylene glycol (meth)acrylate (the number of propylene glycol units is preferably, for example, 2 to 20);

[0063] Mono(meth)acrylates of monohydric or polyhydric alcohols such as 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 3-hydroxybutyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, glycerol mono(meth)acrylate, pentaerythritol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate (the number of ethylene glycol units is preferably 2 to 20, for example), and polypropylene glycol mono(meth)acrylate (the number of propylene glycol units is preferably 2 to 20);

[0064] Poly(meth)acrylates of polyhydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tetra(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate (the number of ethylene glycol units is preferably, for example, 2 to 20), and polypropylene glycol di(meth)acrylate (the number of propylene glycol units is preferably, for example, 2 to 20);

[0065] (Poly)esters of non-polymerizable polybasic acids such as mono[2-(meth)acryloxyethyl]succinate, di[2-(meth)acryloxyethyl]succinate, mono[2-(meth)acryloxyethyl]adipate, di[2-(meth)acryloxyethyl]adipate, mono[2-(meth)acryloxyethyl]phthalate, di[2-(meth)acryloxyethyl]phthalate, and hydroxyalkyl(meth)acrylates;

[0066] (Meth)acrylates containing an amino group, such as 2-aminoethyl (meth)acrylate, 2-(N-methylamino)ethyl (meth)acrylate, 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2-(N-ethylamino)ethyl (meth)acrylate, 2-(N,N-diethylamino)ethyl (meth)acrylate, 3-(N,N-dimethylamino)propyl (meth)acrylate, and 4-(N,N-dimethylamino)butyl (meth)acrylate;

[0067] Epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate, and the like.

[0068] Specific examples of the derivatives of (meth)acrylonitrile include α-chloroacrylonitrile, α-chloromethylacrylonitrile, α-trifluoromethylacrylonitrile, α-methoxyacrylonitrile, α-ethoxyacrylonitrile, and vinylidene cyanide.

[0069] Specific examples of the derivatives of (meth)acrylamide include N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-methoxy(meth)acrylamide, N,N-dimethoxy(meth)acrylamide, N-ethoxy(meth)acrylamide, N,N-diethoxy(meth)acrylamide, diacetone(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N,N-dimethylaminomethyl(meth)acrylamide, N-(2-dimethylamino)ethyl(meth)acrylamide, N,N'-methylenebis(meth)acrylamide, and N,N'-ethylenebis(meth)acrylamide.

[0070] Specific examples of the alkyl vinyl ether include methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether, hexyl vinyl ether, and the like.

[0071] Specific examples of the alkyl vinyl ester include vinyl formate, vinyl acetate, vinyl acrylate, vinyl butyrate, vinyl caproate, and vinyl stearate.

[0072] Specific examples of styrene and derivatives thereof include styrene, α-methylstyrene, vinyltoluene, and the like.

[0073] Among these monomers, (meth)acrylates are preferred, and methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, glycidyl (meth)acrylate, and the like are more preferred; methyl (meth)acrylate and glycidyl (meth)acrylate are further preferred.

[0074] These monomers can be used alone or in combination of two or more.

[0075] In addition, as the component (A-1), a product obtained by chemically bonding the (C) ultraviolet absorber described later to a vinyl copolymer can be used. In this case, the polymer can be obtained, for example, by copolymerizing a (meth) acrylic monomer having an ultraviolet absorbing group in the molecule. Examples of the (meth) acrylic monomer having an ultraviolet absorbing group include benzotriazole compounds represented by the following general formula (4).

[0076] [Chemistry 2]

[0077]

[0078] In the formula, X is a hydrogen atom or a chlorine atom, R 6 is a hydrogen atom, a methyl group or a tertiary alkyl group having 4 to 8 carbon atoms, R 7 is a single bond or a linear or branched alkylene group having 2 to 10 carbon atoms, R 8 It represents a hydrogen atom or a methyl group.

[0079] In the above general formula (4), R 6 The tertiary alkyl group having 4 to 8 carbon atoms includes tert-butyl, tert-pentyl, tert-hexyl, tert-heptyl, tert-octyl, di-tert-octyl and the like.

[0080] As R 7 The alkylene group has 2 to 10 carbon atoms and may be linear or branched. Examples thereof include ethylene, trimethylene, propylene, tetramethylene, 1,1-dimethyltetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, and decamethylene.

[0081] Specific examples of the benzotriazole compounds represented by the general formula (4) include 2-(2'-hydroxy-5'-(meth)acryloyloxyphenyl)-2H-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(meth)acryloyloxymethylphenyl)-2H-benzotriazole, 2-[2'-hydroxy-5'-(2-(meth)acryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-3'-tert-butyl-5'-(2-(meth)acryloyloxyethyl)phenyl]-5-chloro-2H-benzotriazole, and 2-[2'-hydroxy-3'-methyl-5'-(8-(meth)acryloyloxyoctyl)phenyl]-2H-benzotriazole.

[0082] The amount of the ultraviolet absorbing group bonded to the vinyl copolymer is preferably 1 to 20% by mass, more preferably 5 to 15% by mass, in the vinyl copolymer of component (A-1). When the ultraviolet absorbing group is included in an amount of 1% by mass or more, the ultraviolet absorption characteristic becomes good and the weather resistance becomes good, so it is preferred. When the amount is included in an amount of 20% by mass or less, the crack resistance becomes good because the whitening of the film can be prevented, so it is preferred.

[0083] The component (A-1) may be used alone or in combination of two or more.

[0084] As the component (A-1), a polymer having the following structural units (i) to (iii) is particularly preferred. In addition, a vinyl copolymer having an alkoxysilyl group and a UV absorbing group can also be preferably used, and a polymer containing the following structural units (i) to (iv) is more preferred.

[0085] The order of the structural units contained in the component (A-1) is arbitrary, and the component (A-1) may be any of an alternating copolymer, a random copolymer, and a block copolymer.

[0086] [Chemistry 3]

[0087]

[0088] (In the formula, the asterisk * indicates a bond to an adjacent structural unit.)

[0089] The component (A-1) is obtained by adding a free radical polymerization initiator selected from peroxides such as dicumyl peroxide and benzoyl peroxide and azo compounds such as azobisisobutyronitrile to a solution containing the above-mentioned monomers, and subjecting the mixture to a polymerization reaction under heating (for example, at 50 to 150° C., particularly 70 to 120° C., for 1 to 10 hours, particularly 3 to 8 hours).

[0090] The polystyrene-equivalent weight average molecular weight of the vinyl (co)polymer of component (A-1) obtained by gel permeation chromatography (GPC) is preferably 50,000 to 1,000,000, more preferably 60,000 to 800,000. If the molecular weight is 1,000,000 or less, the viscosity will not be excessively increased, and the handling property will be more excellent. If it is 50,000 or more, the appearance defects such as whitening of the film are suppressed, and more excellent adhesion, durability, and weather resistance are obtained.

[0091] (2) (A-2) Alkoxysilyl-free vinyl (co)polymer

[0092] Furthermore, the primer composition of the present invention may contain (A-2) a vinyl copolymer containing no alkoxysilyl group.

[0093] The alkoxysilyl group-free vinyl (co)polymer is not particularly limited, and is obtained by (co)polymerizing a monomer other than the vinyl monomer to which an alkoxysilyl group is bonded via a Si—C bond.

[0094] As the monomer other than the vinyl monomer to which an alkoxysilyl group is bonded via a Si—C bond, which is a raw material of the component (A-2), there may be mentioned the same monomers as those exemplified as other copolymerizable monomers other than the vinyl monomer to which an alkoxysilyl group is bonded via a Si—C bond in the component (A-1), and the same specific examples may also be mentioned.

[0095] The vinyl monomer used as a raw material of the component (A-2) may be used alone or in combination of two or more.

[0096] Among these, (meth)acrylates are preferred, and methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-methylcyclohexyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. are more preferred, and methyl (meth)acrylate is further preferred.

[0097] The polymerization conditions such as reaction temperature, time and polymerization initiator are not particularly limited and can be carried out under known conditions. For example, it can be easily obtained by using a free radical polymerization initiator selected from peroxides such as dicumyl peroxide and benzoyl peroxide and azo compounds such as azobisisobutyronitrile, for example, reacting at 50 to 150° C., especially 70 to 120° C., for 1 to 10 hours, especially 3 to 8 hours.

[0098] As the component (A-2), a commercially available product can be used, and specific examples thereof include (meth)acrylate resins such as Dianal (registered trademark) BR-85, BR-88, and LR-1065 manufactured by Mitsubishi Rayon Co., Ltd., and the like.

[0099] The component (A-2) may be used alone or in combination of two or more.

[0100] The weight average molecular weight of component (A-2) in terms of polystyrene obtained by GPC is preferably 50000 to 1000000, more preferably 60000 to 800000. If the molecular weight is too large, the viscosity may be excessively increased, making synthesis difficult or making handling difficult, while if the molecular weight is too small, poor appearance such as whitening of the film may occur, or sufficient adhesion, durability, and weather resistance may not be obtained.

[0101] When the components (A-1) and (A-2) are used together, the weight average molecular weight of the components (A-1) and (A-2) as a whole, as measured by GPC, in terms of polystyrene, is preferably 6,000 to 1,000,000, and more preferably 50,000 to 800,000. If the molecular weight is too large, the viscosity may be excessively increased, making synthesis difficult or making handling difficult, while if the molecular weight is too small, poor appearance such as whitening of the film may occur, or sufficient adhesion, durability, and weather resistance may not be obtained.

[0102] When the components (A-1) and (A-2) are used together, the mass mixing ratio of the components (A-1) and (A-2) is preferably (A-1): (A-2) = 3:1 to 1:3, more preferably (A-1): (A-2) = 2:1 to 1:2, and further preferably (A-1): (A-2) = 3:2 to 2:3. If the amount of (A-1) is too large, the film may suffer from poor appearance such as whitening, or may not have sufficient adhesion, durability, and weather resistance. If the amount of (A-2) is too large, the viscosity may be excessively increased, making it difficult to handle, and the adhesion, durability, and weather resistance of the film may become insufficient.

[0103] [(B) Inorganic particles]

[0104] (B) component is an inorganic particle having a median diameter of 1 to 100 nm measured by dynamic light scattering. As the above-mentioned inorganic particles, for example, particles of known inorganic oxides such as silicon dioxide, aluminum oxide, cerium oxide, zirconium oxide, zinc oxide, titanium oxide, etc. can be used alone or in combination of two or more. Among these, particles of silicon dioxide, zinc oxide, titanium oxide and cerium oxide are preferred.

[0105] By using the above particles, the hardness and scratch resistance of the film can be improved. In addition, by using particles of cerium oxide, zirconium oxide, zinc oxide, titanium oxide, etc., the ultraviolet shielding ability can be further improved. Among the above particles, silicon dioxide particles and / or zinc oxide particles are particularly preferred because of their good film appearance and weather resistance.

[0106] The median diameter of the volume particle size distribution of the inorganic particles measured by dynamic light scattering is 1 to 100 nm, preferably 3 to 50 nm, and more preferably 5 to 40 nm. If the median diameter exceeds 100 nm, the transparency of the film is insufficient due to light scattering in the visible region. In addition, if the median diameter is less than 1 nm, the hardness, scratch resistance, and weather resistance of the film are poor.

[0107] In the present invention, a device such as Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) can be used for the measurement by the dynamic light scattering method.

[0108] The amount of the inorganic particles is 1 to 19 parts by mass, preferably 3 to 16 parts by mass, and more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the vinyl (co)polymer of the component (A). If it is less than 1 part by mass, the weather resistance is insufficient, and if it exceeds 19 parts by mass, the film has poor appearance such as reduced adhesion and whitening, and cracks are easily generated during the weather resistance test, resulting in poor weather resistance.

[0109] The primer composition preferably contains (C) an ultraviolet absorber and (D) a hindered amine-based light stabilizer as an ultraviolet stabilizer for the purpose of preventing yellowing and surface degradation of the resin substrate.

[0110] [(C) Ultraviolet light absorber]

[0111] As described above, the ultraviolet light absorber of component (C) may be contained in the form of chemical bonding with the vinyl (co)polymer of component (A-1), or may be contained as an additive. When introduced as an additive, benzophenone derivatives, benzotriazole derivatives, cyanoacrylate derivatives, triazine derivatives, etc. are preferred. Specific examples include 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-benzyloxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-diethoxybenzophenone, 2,2'-dihydroxy-4,4'-dipropoxybenzophenone, 2,2'-dihydroxy-4,4'-dibutoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-propoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-butoxybenzophenone, Benzophenone, 2,3,4-trihydroxybenzophenone; 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole; (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)phenol, Tinuvin 400 (manufactured by BASF), Tinuvin 405 (manufactured by BASF), Tinuvin 460 (manufactured by BASF), Tinuvin 477 (manufactured by BASF), Tinuvin 479 (manufactured by BASF), Tinuvin 1577ED (manufactured by BASF), Tinuvin 1600 (manufactured by BASF), etc.

[0112] These organic ultraviolet absorbers may be used alone or in combination of two or more. It is preferred to use two or more of them in combination, and it is particularly preferred to use a triazine derivative and a benzophenone derivative in combination.

[0113] When using an ultraviolet absorber, the amount thereof is preferably 2 to 50 parts by mass, more preferably 10 to 30 parts by mass, relative to 100 parts by mass of the above-mentioned component (A). If it is 2 parts by mass or more, the weather resistance is further improved, and if it is 50 parts by mass or less, it is possible to suppress the poor appearance of the film such as the decrease in the adhesion of the film and whitening.

[0114] When a triazine derivative is used as the ultraviolet absorber, the amount is preferably 1 to 10 parts by mass, more preferably 2 to 5 parts by mass, relative to 100 parts by mass of the above-mentioned component (A). When 1 part by mass or more of the triazine derivative is included, the ultraviolet absorption characteristics become good and the weather resistance becomes good, so it is preferred. When 10 parts by mass or less is included, the whitening of the film can be prevented and the crack resistance becomes good, so it is preferred.

[0115] When a benzophenone derivative is used as the ultraviolet absorber, the amount thereof is preferably 7 to 40 parts by mass, more preferably 10 to 25 parts by mass, relative to 100 parts by mass of the above-mentioned component (A). When 7 parts by mass or more of the benzophenone derivative is included, the ultraviolet absorption characteristics become good and the weather resistance becomes good, so it is preferred. When 40 parts by mass or less is included, the whitening of the film can be prevented and the crack resistance becomes good, so it is preferred.

[0116] [(D) Hindered amine light stabilizer]

[0117] The primer composition preferably contains (D) a hindered amine light stabilizer. In particular, a hindered amine light stabilizer having one or more cyclic hindered amine structures in the molecule, having good compatibility with the primer composition used in the present invention, and having low volatility is preferred.

[0118] Specific examples of hindered amine light stabilizers include 3-dodecyl-1-(2,2',6,6'-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-methyl-3-dodecyl-1-(2,2',6,6'-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-acetyl-3-dodecyl-1-(2,2',6,6'-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, sebacic acid, Bis(2,2',6,6'-tetramethyl-4-piperidinyl) ester, bis(1,2,2',6,6'-pentamethyl-4-piperidinyl) sebacate, tetrakis(2,2',6,6'-tetramethyl-4-piperidinyl) 1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2',6,6'-pentamethyl-4-piperidinyl) 1,2,3,4-butanetetracarboxylate, Tinuvin 123 (manufactured by BASF), Tinuvin 2 49 (manufactured by BASF), Tinuvin 622-SF (manufactured by BASF), Tinuvin 765 (manufactured by BASF), condensation product of 1,2,3,4-butanetetracarboxylic acid, 2,2',6,6'-tetramethyl-piperidinol and tridecanol, 8-acetyl-3-dodecyl-7,7',9,9'-tetramethyl-1,3,8-triazaspiro[4,5]decane-2,4-dione, 1,2,3,4-butane A condensation product of a tetracarboxylic acid with 1,2,6,6'-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5']undecane)diethanol, and a condensation product of 1,2,3,4-butanetetracarboxylic acid with 2,2',6,6'-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-3,9-(2,4,8,10-tetraoxaspiro[5,5']undecane)diethanol. In addition, for the purpose of fixing the light stabilizer, the light stabilizer modified by silanization in Japanese Patent Publication No. 61-56187 can be listed, such as 2,2,6,6-tetramethylpiperidino-4-propyltrimethoxysilane, 2,2',6,6'-tetramethylpiperidino-4-propylmethyldimethoxysilane, 2,2',6,6'-tetramethylpiperidino-4-propyltriethoxysilane, 2,2',6,6'-tetramethylpiperidino-4-propylmethyldiethoxysilane, and their (partial) hydrolyzates, etc. These light stabilizers can be used alone or in combination of two or more. Among these, neutral hindered amine light stabilizers (TINUVIN249, BASF Japan (strain) system) are preferred.

[0119] When a hindered amine light stabilizer is used, its blending amount is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and further preferably 1 to 5 parts by mass relative to 100 parts by mass of the above-mentioned component (A). If it is 0.1 parts by mass or more, weather resistance becomes good, so it is preferred, and if it is 10 parts by mass or less, it is preferred because it can suppress poor film appearance such as decreased adhesion and whitening of the film.

[0120] [(E) Solvent]

[0121] The primer composition may contain a solvent. The solvent is not particularly limited as long as it can dissolve or disperse the above-mentioned components, but an organic solvent with high polarity is preferred.

[0122] Specific examples of organic solvents include alcohols such as methanol, ethanol, isopropanol, n-butanol, isobutanol, tert-butanol, cyclohexanol, and diacetone alcohol; ketones such as methyl ethyl ketone, methyl propyl ketone, diethyl ketone, methyl isobutyl ketone, cyclohexanone, and diacetone alcohol; ethers such as dipropyl ether, dibutyl ether, anisole, dioxane, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate; esters such as ethyl acetate, propyl acetate, butyl acetate, and cyclohexyl acetate, and one or a mixture of two or more thereof can be used. Among these, ethers are preferred, and propylene glycol monomethyl ether is more preferred.

[0123] When a solvent is used, the amount thereof is preferably 1 to 50% by mass, more preferably 5 to 30% by mass, of the solid content concentration of the primer composition. If it is outside this range, disadvantages may occur in the film formed by curing the composition. That is, if the concentration is less than the above range, sagging, warping, and spots may occur in the film, and the required hardness and scratch resistance may not be obtained. In addition, if the concentration exceeds the above range, blushing, whitening, and cracks of the film may occur easily.

[0124] [Other ingredients]

[0125] The primer composition may contain a dispersant or the like as the (B) inorganic particle component as necessary within a range not inhibiting the effects of the present invention.

[0126] Examples of the dispersant include cationic surfactants, anionic surfactants, nonionic surfactants, and various silane compounds or siloxane compounds reactive with the particle surface, such as silane coupling agents.

[0127] The above-mentioned primer composition absorbs water during storage or use, and the alkoxysilyl groups in the vinyl (co)polymer (A) are hydrolyzed, which may reduce the storage stability. In order to prevent this, a dehydrating agent may be added.

[0128] Specific examples of the dehydrating agent include orthocarboxylic acid esters such as methyl orthoformate, ethyl orthoformate, and ethyl orthoacetate; dialkylcarbodiimides such as dicyclohexylcarbodiimide; and solid adsorbents such as silica gel and molecular sieves.

[0129] The primer composition may contain leveling agents, metal powders, antioxidants, infrared reflective / absorptive agents, flexibility imparting agents, antistatic agents, antifouling imparting agents, water repellent imparting agents, etc., as needed, within a range that does not hinder the effects of the present invention.

[0130] The primer composition preferably has a liquid pH of 2 to 8, more preferably 3 to 6, from the viewpoint of storage stability. When the pH is outside this range, storage stability may be reduced.

[0131] There is no particular limitation on the method for adjusting the pH, and a pH adjusting agent may be added to adjust the pH to the above range. When the pH of the primer composition is outside the above range, if it is on the acidic side compared to the range, a basic compound such as ammonia or ethylenediamine may be added to adjust the pH, and if it is on the alkaline side, an acidic compound such as hydrochloric acid, nitric acid, acetic acid, or citric acid may be used to adjust the pH.

[0132] The primer composition used in the present invention can be obtained by mixing the above-mentioned components according to a conventional method.

[0133] Furthermore, the primer layer can be formed by applying the obtained primer composition on a resin substrate and curing the composition.

[0134] Examples of the method for applying the primer composition include various coating methods such as brush coating, spray coating, dipping, flow coating, roll coating, curtain coating, spin coating, and knife coating.

[0135] The curing method after applying the primer composition may be to allow it to dry in the air or to heat it. There is no particular limitation on the curing temperature and curing time, but for example, it is preferably heated at a temperature below the heat resistance temperature of the substrate for 10 minutes to 2 hours, and more preferably heated at 80 to 135° C. for 30 minutes to 2 hours.

[0136] The thickness of the primer layer needs to be 1 to 20 μm, preferably 3 to 15 μm, and more preferably 5 μm or more and less than 10 μm, in order to satisfy the hardness, scratch resistance, long-term stable adhesion, and no cracking of the film. If the film thickness is less than 1 μm, the ultraviolet shielding ability is insufficient, and the film peeling occurs. If the film thickness exceeds 20 μm, cracks will occur in the film.

[0137] <Hard coating>

[0138] The coated article of the present invention has a hard coating layer formed on the primer layer.

[0139] The hard coat layer in the coated article of the present invention is a cured film of a silicone composition containing the following components (a) to (c).

[0140] (a) is selected from the following formula (1):

[0141] R 1 m Si(OR 2 ) 4-m (1)

[0142] (Where R 1 are each independently a hydrogen atom, or a substituted or unsubstituted monovalent hydrocarbon group, R 2 Each is independently an alkyl group having 1 to 3 carbon atoms, and m is 0, 1 or 2.

[0143] An organic silicone resin obtained by (co)hydrolyzing and condensing at least one of the alkoxysilanes represented by

[0144] (b) colloidal silicon dioxide,

[0145] (c) Ultraviolet light absorber

[0146] [(a)Component]

[0147] The component (a) is a silicone resin obtained by (co)hydrolyzing and condensing at least one selected from the group consisting of alkoxysilane represented by the following general formula (1) and its (partial) hydrolysis-condensation product.

[0148] R 1 m Si(OR 2 ) 4-m (1)

[0149] In the formula, R 1 Each of the R 1 can be bonded to each other to form a linking group, R 2 Each independently represents an alkyl group having 1 to 3 carbon atoms, and m represents 0, 1 or 2.

[0150] R 1The monovalent hydrocarbon group may be any of linear, branched and cyclic, and includes alkyl groups having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, and more preferably 1 to 6 carbon atoms; cycloalkyl groups having 3 to 12 carbon atoms, preferably 3 to 8 carbon atoms, and more preferably 3 to 6 carbon atoms; alkenyl groups having 2 to 12 carbon atoms, preferably 2 to 8 carbon atoms, and more preferably 2 to 6 carbon atoms; and aryl groups having 6 to 12 carbon atoms, preferably 6 to 8 carbon atoms.

[0151] As R 1 Specific examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, and octyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; alkenyl groups such as vinyl and allyl; and aryl groups such as phenyl.

[0152] In addition, part or all of the hydrogen atoms of these groups may be substituted by other substituents, and specific examples thereof include halogen-substituted hydrocarbon groups such as chloromethyl, γ-chloropropyl, and 3,3,3-trifluoropropyl; (meth)acryloyloxy, epoxy, mercapto, amino, and isocyanate-substituted hydrocarbon groups such as γ-(meth)acryloyloxypropyl, γ-glycidyloxypropyl, 3,4-epoxycyclohexylethyl, γ-mercaptopropyl, γ-aminopropyl, and γ-isocyanatepropyl; and the like. In addition, isocyanurate groups bonded to a plurality of isocyanate-substituted hydrocarbon groups may also be exemplified.

[0153] Among these, when used in applications requiring scratch resistance and weather resistance, an alkyl group is preferred, and when toughness and dyeability are required, an epoxy group, a (meth)acryloyloxy group, and an isocyanurate-substituted hydrocarbon group are preferred.

[0154] As R 2 The alkyl group having 1 to 3 carbon atoms can be exemplified by methyl, ethyl, n-propyl, and isopropyl. Among these, if the high reactivity of hydrolysis and condensation and the generated alcohol R are considered, 2 Since OH has a high vapor pressure and can be easily removed by distillation, a methyl group or an ethyl group is preferred.

[0155] In the above formula (1), when m=0, the general formula: Si(OR 2)4 and its partial hydrolysis condensate (a-0) include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetrabutoxysilane, partial hydrolysis condensate of tetramethoxysilane (trade name "MSilicate 51", manufactured by Tama Chemical Industry Co., Ltd., trade name "MSI51", Colcoat Co., Ltd., trade name "MS51", "MS56", manufactured by Mitsubishi Chemical Co., Ltd.), partial hydrolysis condensate of tetraethoxysilane (trade name "Silicate 35", "Silicate 45", manufactured by Tama Chemical Industry Co., Ltd., trade name "ESI40", "ESI48", Colcoat Co., Ltd.), partial hydrolysis condensate of tetramethoxysilane and tetraethoxysilane (trade name "FR-3", manufactured by Tama Chemical Industry Co., Ltd., trade name "EMSi48", Colcoat Co., Ltd.), Co., Ltd. manufacturing) etc.

[0156] In the above formula (1), when m=1, the general formula: R 1 Si(OR 2Specific examples of the trialkoxysilane (a-1) represented by )3 and its partially hydrolyzed condensate include hydrogen trimethoxysilane, hydrogen triethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, methyl triisopropoxysilane, ethyl trimethoxysilane, ethyl triethoxysilane, ethyl triisopropoxysilane, propyl trimethoxysilane, propyl triethoxysilane, propyl triisopropoxysilane, phenyl trimethoxysilane, vinyl trimethoxysilane, Alkane, allyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-acryloxypropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-chloropropyl trimethoxysilane, 3,3 , 3-trifluoropropyl trimethoxysilane, 3,3,3-trifluoropropyl triethoxysilane, perfluorooctylethyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-(2-aminoethyl)aminopropyl trimethoxysilane, γ-isocyanate propyl trimethoxysilane, γ-isocyanate propyl triethoxysilane, tris(3-trifluoropropyl)silane bonded between isocyanate groups isocyanurate, tris(3-triethoxysilylpropyl) isocyanurate, a partially hydrolyzed condensate of methyltrimethoxysilane (trade name "KC-89S", "X-40-9220", manufactured by Shin-Etsu Chemical Co., Ltd.), a partially hydrolyzed condensate of methyltrimethoxysilane and γ-glycidyloxypropyltrimethoxysilane (trade name "X-41-1056", manufactured by Shin-Etsu Chemical Co., Ltd.), and the like.

[0157] In the above formula (1), when m=2, the general formula: R 1 2Si(OR 2Specific examples of the dialkoxysilane represented by )2 and its (partial) hydrolysis condensate (a-2) include methyl hydrogen dimethoxysilane, methyl hydrogen diethoxysilane, dimethyl dimethoxysilane, dimethyl diethoxysilane, methyl ethyl dimethoxysilane, diethyl dimethoxysilane, diethyl diethoxysilane, methyl propyl dimethoxysilane, methyl propyl diethoxysilane, diisopropyl dimethoxysilane, phenyl methyl dimethoxysilane, vinyl methyl dimethoxysilane, Silane, γ-glycidyloxypropylmethyldimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, β-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)aminopropylmethyldimethoxysilane, etc.

[0158] The silicone resin of component (a) can be prepared by using the components (a-0), (a-1) and (a-2) in any ratio. Furthermore, when it is desired to improve storage stability, scratch resistance and crack resistance, it is preferably used in a ratio of 0 to 50% of silicon atoms from (a-0), 50 to 100% of silicon atoms from (a-1) and 0 to 50% of silicon atoms from (a-2) relative to the total number of Si atoms of (a-0), (a-1) and (a-3). It is more preferably used in a ratio of 0 to 30% of silicon atoms from (a-0), 70 to 100% of silicon atoms from (a-1) and 0 to 30% of silicon atoms from (a-2). In this case, if (a-1) as the main component is 50% or more, curability is good and the hardness of the cured film becomes appropriate, which is preferred.

[0159] When the silicone resin of component (a) is produced, components (a-0), (a-1) and (a-2) can be (co)hydrolyzed and condensed by a known method. For example, the silicone resin can be obtained by (co)hydrolyzing and condensing the alkoxysilane or (partial) hydrolysis condensate of components (a-0), (a-1) and (a-2) or a mixture thereof in water having a pH of 1 to 7.5, preferably 2 to 7. In this case, a product obtained by dispersing metal oxide microparticles such as silica sol in water can be used. In order to adjust to this pH range and to promote hydrolysis, inorganic acids and organic acids such as hydrogen fluoride, hydrochloric acid, nitric acid, formic acid, acetic acid, propionic acid, oxalic acid, citric acid, maleic acid, benzoic acid, malonic acid, glutaric acid, glycolic acid, methanesulfonic acid, toluenesulfonic acid, or solid acid catalysts such as cation exchange resins having carboxylic acid groups or sulfonic acid groups on the surface, or water-dispersed metal oxide microparticles such as acidic water-dispersed silica sol can be used as catalysts. In addition, during the hydrolysis, a product obtained by dispersing metal oxide fine particles such as silica sol in water or an organic solvent may coexist.

[0160] In the hydrolysis step, the amount of water used is preferably 20 to 3000 parts by mass relative to 100 parts by mass of the total of components (a-0), (a-1) and (a-2). Excessive use of water may not only reduce the efficiency of the device, but also reduce the coating and drying properties due to the influence of residual water in the final composition. Furthermore, in order to improve storage stability, scratch resistance and crack resistance, it is preferably 50 parts by mass or more and less than 150 parts by mass.

[0161] The hydrolysis step may be performed by dripping or adding water to the alkoxysilane or its (partial) hydrolysis condensate, or conversely, by dripping or adding the alkoxysilane or its (partial) hydrolysis condensate into water. In this case, the reaction solvent may contain an organic solvent, but preferably does not contain an organic solvent. This is because the more organic solvent is contained, the smaller the molecular weight of the obtained silicone resin tends to be.

[0162] The condensation step may be carried out continuously following the hydrolysis step, and is usually carried out at a liquid temperature of room temperature or under heating of 100°C or less. At a temperature higher than 100°C, gelation may occur. Furthermore, condensation can be promoted by distilling off the alcohol generated by hydrolysis at 80°C or more and under normal pressure or reduced pressure. Furthermore, a condensation catalyst such as a basic compound, an acidic compound, or a metal chelate compound may be added for the purpose of promoting condensation.

[0163] Before or during the condensation process, an organic solvent may be added for the purpose of adjusting the degree and concentration of condensation. In addition, a product obtained by dispersing metal oxide particles such as silica sol in water or an organic solvent may be added. Generally, as the condensation proceeds, the organosilicon resin forms a high molecular weight and its solubility in water and the generated alcohol decreases. Therefore, as the organic solvent to be added, it is preferred to use an organic solvent with a high polarity that fully dissolves the organosilicon resin and has a boiling point of 80°C or above.

[0164] Specific examples of such organic solvents include alcohols such as isopropyl alcohol, n-butanol, isobutyl alcohol, tert-butanol, cyclohexanol, and diacetone alcohol; ketones such as methyl propyl ketone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, cyclohexanone, and diacetone alcohol; ethers such as dipropyl ether, dibutyl ether, anisole, dioxane, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monomethyl ether acetate; esters such as propyl acetate, butyl acetate, and cyclohexyl acetate; and the like.

[0165] The polystyrene-equivalent weight average molecular weight of the obtained silicone resin in GPC analysis is preferably 1500 to 50000, and more preferably 2000 to 20000. When the molecular weight is 1500 or more, the toughness of the film is excellent and the generation of cracks can be suppressed, and when the molecular weight is 50000 or less, the film whitening due to excessive reduction in hardness and resin phase separation in the film can be suppressed.

[0166] [(b) Component]

[0167] The component (b) is colloidal silica. The colloidal silica of the component (b) is preferably in the form of colloidal dispersion of silica in a medium such as water or an organic solvent, and commercially available water-dispersible or organic-dispersible silica can be used.

[0168] Specific examples include SNOWTEX-O, OS, O40, OL, methanol silica sol, IPA-ST, IBA-ST, PMA-ST, and MEK-ST manufactured by Nissan Chemical Co., Ltd.

[0169] As silica, from the viewpoint of transparency and hardness of the obtained hard coating layer, silica having a median diameter of 5 to 50 nm as measured by a dynamic light scattering method is preferred.

[0170] The amount of colloidal silica added is preferably 3 to 100 parts by mass, more preferably 6 to 50 parts by mass, and even more preferably 10 to 30 parts by mass, based on solid content per 100 parts by mass of the component (a).

[0171] [(c) Component]

[0172] The component (c) is a UV absorber. Examples of the UV absorber of the component (c) include benzophenone derivatives, benzotriazole derivatives, cyanoacrylate derivatives, and triazine derivatives.

[0173] Specific examples thereof include 2,4-dihydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-benzyloxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone ...octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-n Oxybenzophenone, 2,2'-dihydroxy-4,4'-diethoxybenzophenone, 2,2'-dihydroxy-4,4'-dipropoxybenzophenone, 2,2'-dihydroxy-4,4'-dibutoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-propoxybenzophenone, 2,2'-dihydroxy-4-methoxy-4'-butoxybenzophenone, 2,3,4-trihydroxybenzophenone; 2-(2 -hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole; (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy)phenol, Tinuvin 400 (manufactured by BASF), Tinuvin 405 (manufactured by BASF), Tinuvin 460 (manufactured by BASF), Tinuvin 477 (manufactured by BASF), Tinuvin 479 (manufactured by BASF), Tinuvin 1577ED (manufactured by BASF), Tinuvin 1600 (manufactured by BASF), etc. In addition, a silane coupling type reactive ultraviolet absorber in which a part of the above compounds is substituted with an alkoxysilyl group can be used.

[0174] Among these, a silane coupling type reactive UV absorber in which a part of the above compounds is substituted with an alkoxysilyl group is preferred. By using the above reactive UV absorber, the UV absorbing group is fixed in the hard coat layer, and precipitation of the UV absorber over time is suppressed, which is effective in suppressing whitening and cracking.

[0175] The reactive ultraviolet absorber is preferably a benzophenone derivative represented by the following general formula (2) and having one or more alkoxysilyl groups.

[0176] [Chemistry 4]

[0177]

[0178] In the formula, R 3are each independently a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 5 carbon atoms, or a group represented by the following general formula (3), R 3 At least one of them is a group represented by the following general formula (3).

[0179] *-O-(CH2) j -SiR 4 k (OR 5 ) 3-k (3)

[0180] (Where R 4 and R 5 Each is independently an alkyl group having 1 to 5 carbon atoms, j is an integer of 1 to 8, and k is an integer of 0 to 2. The asterisk * indicates a bond to an adjacent atom. )

[0181] In the above formula (2), R 3 The alkyl group has 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, and may be linear or branched. Specific examples thereof include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, and isopentyl.

[0182] Furthermore, R 3 At least one of them is a group represented by the general formula (3). By having a group represented by the general formula (3), the ultraviolet absorber is fixed in the hard coat layer, and precipitation over time is suppressed, which is effective in suppressing whitening and cracking of the hard coat layer.

[0183] In addition, R 3 At least one of them is a hydroxyl group, because the ultraviolet absorption is better, so it is preferred that R 3 In the above, other than the group represented by the general formula (3) and the hydroxyl group, a hydrogen atom is preferred.

[0184] In the above formula (3), R 4 and R 5 The alkyl group having 1 to 5 carbon atoms preferably has 1 to 3 carbon atoms. Specific examples thereof include: 3 The same groups as those exemplified in 4 Methyl and ethyl are preferred. In addition, if the high reactivity of hydrolysis and condensation and the generated alcohol R are taken into consideration, 5 OH has a high vapor pressure and is easy to distill off, R 5 Preferred are methyl and ethyl.

[0185] j is an integer of 1 to 8, preferably an integer of 1 to 3 from the viewpoint of easy availability of raw materials, and j=3 is preferred.

[0186] k is an integer of 0 to 2, and k=0 is particularly preferred because the reactivity of hydrolysis and condensation increases and the scratch resistance of the film improves.

[0187] Among the benzophenone derivatives represented by the above general formula (2), 2-hydroxy-4-trimethoxysilylpropoxybenzophenone is preferred.

[0188] The amount of the component (c) is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, based on 100 parts by mass of the component (a).

[0189] [Curing catalyst]

[0190] The silicone composition preferably contains a curing catalyst that accelerates the condensation reaction of condensable groups such as silanol groups and alkoxy groups contained in the silicone resin (a).

[0191] Specific examples of the curing catalyst include basic compounds such as lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium methoxide, sodium propionate, potassium propionate, sodium acetate, potassium acetate, sodium formate, potassium formate, trimethylbenzylammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetramethylammonium acetate, n-hexylamine, tributylamine, diazabicycloundecene (DBU), and dicyandiamide; metal-containing compounds such as tetraisopropyl titanate, tetrabutyl titanate, titanium acetylacetonate, triisobutoxyaluminum, triisopropoxyaluminum, tri(acetylacetonate)aluminum, diisopropoxy(ethyl acetylacetonate)aluminum, aluminum perchlorate, aluminum chloride, cobalt octoate, cobalt acetylacetonate, iron acetylacetonate, tin acetylacetonate, dibutyltin octoate, and dibutyltin laurate; acidic compounds such as p-toluenesulfonic acid and trichloroacetic acid, and the like. Among these, sodium propionate, sodium acetate, sodium formate, trimethylbenzylammonium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tris(acetylacetonate)aluminum, and diisopropoxy(ethyl acetoacetate)aluminum are particularly preferred.

[0192] When a curing catalyst is used, the amount thereof is not particularly limited as long as it is an amount effective for curing the silicone resin of component (a). Specifically, it is preferably 0.0001 to 1% by mass, more preferably 0.0005 to 0.1% by mass, relative to the solid content of the silicone resin. If it is 0.0001% by mass or more, curing is sufficient, and if it is 1% by mass or less, the generation of cracks in the film and the reduction of water resistance can be suppressed.

[0193] [Solvent]

[0194] The above-mentioned silicone composition preferably contains a solvent. Examples of the solvent include the same solvents as those used in the above-mentioned primer composition. When a solvent is used, the amount thereof is such that the solid content concentration of the silicone composition is preferably 5 to 40% by mass, more preferably 10 to 35% by mass.

[0195] [Other ingredients]

[0196] The above-mentioned silicone composition may contain a pH adjuster, a leveling agent, a thickener, a pigment, a dye, metal oxide particles other than silica, a metal powder, an antioxidant, an ultraviolet stabilizer, an infrared reflectivity / absorption agent, a flexibility agent, an antistatic agent, an antifouling agent, a water repellency agent, etc. as needed within a range not impairing the effects of the present invention.

[0197] The silicone composition used in the present invention can be obtained by mixing the above-mentioned components according to a conventional method.

[0198] Furthermore, the obtained silicone composition can be applied onto the primer layer and cured to form a hard coat layer.

[0199] As a method for applying the silicone composition, the same method as exemplified for the primer composition can be mentioned.

[0200] As a curing method after applying the above-mentioned silicone composition, it can be placed in the air to dry, or it can be heated. There is no particular limitation on the curing temperature and curing time. For example, it is preferably heated below the heat resistance temperature of the substrate for 10 minutes to 2 hours, and more preferably heated at 80 to 135°C for 30 minutes to 2 hours.

[0201] The thickness of the obtained hard coating is not particularly limited. In order to satisfy the hardness, scratch resistance, long-term stable adhesion and no cracking of the film, it must be 1 to 15 μm, preferably 3 to 13 μm, and more preferably 5 to 10 μm. If the thickness is less than 1 μm, the ultraviolet shielding ability is insufficient, the film peeling occurs, and the hardness and scratch resistance of the film are insufficient. In addition, if the film thickness exceeds 15 μm, cracks will be generated in the film.

[0202] [Hardness of hard coating]

[0203] The surface hardness of the hard coating layer measured by nanoindentation is preferably 0.10 to 0.50 GPa, more preferably 0.20 to 0.40 GPa, and further preferably 0.25 to 0.35 GPa. As an apparatus for measuring the elastic modulus of such a film, a nanoindenter (Hysitron Triboindenter, manufactured by Bruker Japan KK; ENT-NEXUS, manufactured by Elionix, Inc.) and the like can be cited.

[0204] When the surface hardness is 0.10 GPa or more, the wear resistance when the light-modified layer is formed becomes good, so it is preferred. When the surface hardness is 0.50 GPa or less, the stress of the light-modified layer from the resin substrate can be effectively alleviated by the siloxane-based hard coating during the heat resistance test and the weather resistance test, so the crack resistance is improved, and the heat resistance and weather resistance of the film become good, so it is preferred.

[0205] Furthermore, in the present invention, the above-mentioned hardness is a value obtained by using a nanoindenter (ENT-NEXUS, manufactured by Elionix, Inc.) to analyze the data obtained when a Berkovich-type indenter is pressed into the surface of the silicone hard coating with an indentation load of 0.5 mN at room temperature 23°C using dedicated software.

[0206] <Light-modifying layer>

[0207] The coated article of the present invention has a light-modifying layer formed on the surface layer portion of the hard coat layer.

[0208] The light-modifying layer in the coated article of the present invention is preferably a hard thin film layer containing silicon dioxide as a main component, which is obtained by irradiating the surface of the hard coating layer with light having a wavelength of 300 nm or less.

[0209] It is known that the energy of short-wavelength light below 300 nm can cut the bond chains of organic polymers, selectively cut the CH, Si-C, and Si-O-Si bonds constituting the side chain functional groups in the hard coating layer formed on the substrate in sequence, and then allow the cleaved oxygen atoms to rebond with silicon atoms, thereby modifying a portion of the hard coating layer into a hard thin film layer with silicon dioxide as the main component.

[0210] As the light source of the vacuum ultraviolet of the short wavelength below 300nm, can list excimer laser, excimer lamp, low pressure mercury lamp etc.As excimer laser, can list the Ar2 laser with the wavelength of 126nm, the F2 laser with the wavelength of 157nm, the ArF excimer laser with the wavelength of 193nm, the KrF excimer laser with the wavelength of 248nm, the XeCl excimer laser with the wavelength of 307nm etc.Wherein, the light source of the vacuum ultraviolet below 300nm is Ar2 laser, F2 laser, ArF laser, KrF excimer laser. In addition, excimer lamps exist as wavelengths of 126nm (Ar2), 146nm (Kr2), 165nm (ArBr), 172nm (Xe2), 175nm (ArCl), 193nm (ArF), 207nm (KrBr), 222nm (KrCl), 253nm (XeCl), 283nm (XeBr), 308nm (XeCl). In the present invention, it is preferred to use F2 lasers and Xe excimer lamps.

[0211] There is no particular limitation on the method of ultraviolet irradiation. For example, there can be mentioned a method of irradiating the hard coating layer with ultraviolet light having a wavelength of 300 nm or less using the above-mentioned light source in the air or an inert gas atmosphere such as nitrogen or argon. The accumulated light intensity is preferably 0.1 J / cm 2 More preferably 0.5 J / cm 2 above.

[0212] The film thickness of the photomodification layer is preferably 0.1 to 1.0 μm, more preferably 0.2 to 0.8 μm, and further preferably 0.3 to 0.6 μm. When the film thickness is 0.1 μm or more, abrasion resistance becomes good, so it is preferred. In addition, when the film thickness is 1.0 μm or less, heat resistance and weather resistance become good, so it is preferred.

[0213] <Other floors>

[0214] The coated article of the present invention may further have an ultraviolet absorbing layer, a printing layer, a recording layer, an infrared shielding layer, a pressure-sensitive adhesive layer, an inorganic vapor-deposited film layer, etc. on the above-mentioned light-modifying layer.

[0215] The visible light transmittance of the film of the coated article of the present invention is one of the characteristics. As an indicator thereof, the haze value of the film can be used for evaluation. Since the haze increases with the thickness of the film, the haze increases, so in the present invention, the haze of a film thickness of less than 20 μm is preferably less than 2.0, more preferably less than 1.5, and further preferably less than 1.0. The haze of the film can be measured, for example, using a turbidity meter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.).

[0216] One of the characteristics of the coated article of the present invention is the good adhesion between the film and the substrate. As an indicator thereof, a checkerboard peeling test according to JIS K5400 can be used for evaluation. Using a razor blade, 6 cuts are formed in the film at intervals of 2 mm in the vertical and horizontal directions to make 25 checkerboards, and after Cellotape (registered trademark, (manufactured by Nichiban Co., Ltd.) is well adhered, when it is peeled off sharply in the 90° forward direction, the number of grids (X) remaining without peeling off the film is considered. The closer the value of the number of grids (X) when expressed as X / 25 is to 25, the better the adhesion can be said to be. In addition, the substrate with the cured film is boiled in water at 100°C for 2 hours, and the same grid test is performed, which can be used as an indicator of water-resistant adhesion.

[0217] One of the characteristics of the coated article of the present invention is that it has excellent scratch resistance. As an indicator thereof, the difference in haze (ΔHz) before and after the test in the Taper wear test can be used for evaluation. According to ASTM1044, a wear wheel CS-10F is installed in the Taper wear tester, and when the ΔHz (% point) of the haze after 1000 revolutions under a load of 500gf is evaluated by (haze after the test (%)) - (haze before the test (%)), the ΔHz of a film thickness of less than 20μm is preferably less than 10 points, more preferably less than 5 points, and further preferably less than 2 points. In this field, when the haze difference (ΔHz) is less than 2 points in the above test, it is generally judged to have scratch resistance equal to or higher than that of glass.

[0218] One of the characteristics of the coated article of the present invention is good heat resistance. As an example of a heat resistance test, a method of evaluating the coated article by storing it in an oven at 110°C for 100 to 1000 hours and observing the appearance of the test piece every 100 hours can be cited. The coated article of the present invention preferably does not produce cracks or peeling in the film after a 200-hour test, more preferably does not produce cracks or peeling in the film after a 500-hour test, and most preferably does not produce cracks or peeling in the film after a 1000-hour test.

[0219] The coated article of the present invention has good weather resistance as one of its characteristics. As an indicator, the change in the appearance of the film in the weather resistance test of the film can be used to determine it. As an example of a weather resistance test, it can be cited that the film is irradiated with ultraviolet rays for 4 hours (irradiation intensity 90mW / cm 2The method of evaluating the test piece is to observe the state of the test piece every 10 cycles for 120 hours, with 12 hours of 4 hours of darkness (blackboard temperature 63°C, humidity 70%), 4 hours of condensation (blackboard temperature 30°C, humidity 95%) as one cycle. The observation method can be visual or microscopic. There is no particular limitation on the microscope that can be used for such a purpose, and examples thereof include a laser microscope (manufactured by KEYANCE Co., Ltd., device name "VK-8710").

[0220] In the weather resistance test, preferably no cracks or peeling occurs in the film even after 360 hours of testing, more preferably no cracks or peeling occurs in the film even after 480 hours of testing, and even more preferably no cracks or peeling occurs in the film even after 600 hours of testing.

[0221] In the above weather resistance test, 1 / 3 of the test time was spent on light irradiation at an intensity of 900 W / m 2 . 900W / m 2 The accumulated energy of ultraviolet light irradiation for 1 hour is 0.9 kWh / m 2 According to the rule of transformation of assembly units, it is equal to 3.24MJ (megajoules). Therefore, the cumulative exposure after 600 hours of the above SUV test becomes 600 (test time) × 1 / 3 (ratio of light exposure test) × 3.24 (MJ / m 2 h)≈648(MJ / m 2 ).

[0222] The test conditions and environment of the weather resistance test in the present invention can be set arbitrarily, and the correlation between the test conditions and outdoor exposure can be easily estimated. For example, if the outdoor ultraviolet light is measured using an ultraviolet light meter (EYE ultraviolet light meter UVP365-1, manufactured by Iwasaki Electric Co., Ltd.), it can be found that it is 1×101 W / m 2 (Measured at noon on the spring equinox in Matsui-da-cho, Annaka City, Gunma Prefecture on a clear day.) The average annual sunshine hours in Japan are about 2,000 hours, so the cumulative radiation dose in Japan for one year can be estimated to be about 2,000 (h / year) × 1 (year) × 10 (W / m 2 )=20(kWh / m 2 )≈72(MJ / m 2 ). Therefore, the cumulative exposure after 600 hours of the SUV test is equivalent to the cumulative exposure of the sample when used outdoors in Japan for about 9 years. 2 , cumulative exposure after 600 hours of testing) / 72(MJ / m 2·year, Japan's annual sunlight exposure) ≈ 9 (year). The outdoor environment varies depending on latitude and climate, so the test conditions can be appropriately changed according to the use environment of the cured film.

[0223] Example

[0224] The following shows synthesis examples, embodiments and comparative examples to specifically illustrate the present invention, but the present invention is not limited by the following embodiments. It should be noted that in the following examples, % represents mass %, parts represents mass parts, and Me represents methyl. In addition, the weight average molecular weight is measured by gel permeation chromatography (GPC) based on standard polystyrene.

[0225] [1] Synthesis of vinyl copolymer (A-1)

[0226] [Synthesis example 1]

[0227] <Synthesis of Vinyl Copolymer (A-1-1) Having Ultraviolet Absorbing Groups and Alkoxysilyl Groups>

[0228] In a 2-liter flask equipped with a stirrer, a condenser, and a thermometer, 126 g of isobutyl acetate and 126 g of isopropyl alcohol as solvents were placed, and heated to 80° C. under a nitrogen stream. A previously prepared monomer mixed solution (a mixture of 90 g of γ-methacryloxypropyltrimethoxysilane, 270 g of methyl methacrylate, 22.5 g of glycidyl methacrylate, 67.5 g of RUVA-1 (2-[2'-hydroxy-5'-(2-methacryloxyethyl)phenyl]-2H-benzotriazole (RUVA-93, manufactured by Otsuka Chemical Co., Ltd.) as a UV absorbing group, and 1 g of 2,2'-azobis(2-methylbutyronitrile) as a polymerization initiator) was added dropwise at 80 to 90° C. over 1.5 hours, and further stirred at 80 to 90° C. for 5 hours. Then, the mixture was left to cool, and 367 g of diacetone alcohol was added to stop the reaction.

[0229] In the obtained vinyl copolymer having ultraviolet absorbing groups and alkoxysilyl groups (A-1-1), the ratio of ultraviolet absorbing groups was 10.2 mass %, the ratio of trimethoxysilyl groups was 10.2 mass %, and the weight average molecular weight was 87,800.

[0230] [Synthesis example 2]

[0231] <Synthesis of vinyl copolymer having alkoxysilyl group (A-1-2)>

[0232] A vinyl copolymer (A-1-2) having an alkoxysilyl group was obtained by the same operation as in Synthesis Example 1 except that the composition was changed to that shown in Table 1. The ratio of trimethoxysilyl groups in the obtained copolymer was 9.4% by mass and the weight average molecular weight was 60,800.

[0233] [Table 1]

[0234]

[0235] (Note)

[0236] MPTMS: γ-methacryloxypropyltrimethoxysilane

[0237] RUVA-1: 2-[2'-hydroxy-5'-(2-methacryloyloxyethyl)phenyl]-2H-benzotriazole (RUVA-93, manufactured by Otsuka Chemical Co., Ltd.)

[0238] MMA: Methyl Methacrylate

[0239] GMA: Glycidyl Methacrylate

[0240] [2] Synthesis of UV absorbers

[0241] [Synthesis example 3]

[0242] <Synthesis of reactive ultraviolet absorber (c-1)>

[0243] 25.4 g (0.1 mol) of 4-allyloxy-2-hydroxybenzophenone (manufactured by Aldrich) was suspended in 70 mL of toluene in a reactor. 0.05 g of platinum catalyst PL50-T (manufactured by Shin-Etsu Chemical Co., Ltd.) was added thereto, the temperature was raised to 65°C, and 29.3 g (0.24 mol) of trimethoxysilane was added. After stirring at 80°C for 2 hours, the reaction mixture was cooled, 5 g of Wakogel C-100 was added to adsorb the platinum catalyst, and then filtered, and the solvent was removed by reduced pressure concentration to obtain 34.8 g (0.092 mol) of a red oily substance.

[0244] The principal component 1 The H-NMR spectrum was consistent with the structure of 2-hydroxy-4-trimethoxysilylpropoxybenzophenone. The obtained compound was abbreviated as reactive ultraviolet absorber (c-1).

[0245] [3] Preparation of silicone composition

[0246] [Synthesis Example 4]

[0247] <Preparation of silicone composition (HC-1)>

[0248] Into a 500 ml flask equipped with a stirrer, a condenser and a thermometer, 48 g of methyltrimethoxysilane and 1.2 g of the reactive ultraviolet absorber (c-1) obtained in Synthesis Example 3 were added, and the temperature was maintained at 20°C while stirring. 29.4 g of water-dispersed colloidal silica (SNOWTEX O, manufactured by Nissan Chemical Co., Ltd., average particle size 15 to 20 nm, SiO2: 20% content), 8.2 g of acetic acid and 30 g of water were added and stirred.

[0249] After stirring at 60°C for 3 hours, 45 g of n-butanol was added, and a total of 72 g of by-produced methanol and a portion of water were distilled off at normal pressure. Next, a solution diluted with isopropyl alcohol to a solid content concentration of 30% by mass was obtained.

[0250] Next, 0.02 g of polyether-modified silicone KP-341 (manufactured by Shin-Etsu Chemical Co., Ltd.) as a leveling agent and 0.1 g of a 10% by mass aqueous solution of tetrabutylammonium hydroxide as a curing catalyst were added to 30 g of the above solution, and the mixture was stirred at room temperature for 1 hour, filtered with filter paper to remove the precipitate, thereby obtaining a silicone composition (HC-1).

[0251] [Comparative Synthesis Example 1]

[0252] <Preparation of silicone composition (HC-2) not containing ultraviolet absorber>

[0253] The same operation as in Synthesis Example 4 was carried out except that the reactive ultraviolet absorber (c-1) was not added, thereby obtaining a silicone composition (HC-2) containing no ultraviolet absorber.

[0254] [4] Preparation of primer composition

[0255] [Preparation Examples 1 to 8, Comparative Preparation Examples 1 to 6]

[0256] To a composition having the composition shown in Tables 2 and 3 (converted to solid content, parts by mass) prepared according to a conventional method, ethyl orthoformate (F-1) was added as a dehydrating agent to adjust the concentration to 5 mass ppm in the composition, LE-604 (G-1) was added as a leveling agent to adjust the concentration to 500 mass ppm in the composition, and propylene glycol monomethyl ether (E-1) was added to adjust the total solid content concentration to 20 mass %, thereby obtaining a primer composition.

[0257] In addition, among the abbreviations used in Preparation Examples, Examples and Comparative Examples, the abbreviations not described in Synthesis Examples are as follows.

[0258] <(A-2) Ingredients>

[0259] A-2-1: polymethyl methacrylate resin (Dianal BR-88, manufactured by Mitsubishi Rayon Co., Ltd., Mw: 576, 900, Tg: 105°C)

[0260] A-2-2: polymethyl methacrylate resin (Dianal BR-85, manufactured by Mitsubishi Rayon Co., Ltd., Mw: 263,800, Tg: 105°C)

[0261] <(B) Inorganic particles>

[0262] B-1: Propylene glycol monomethyl ether dispersion of silica (PMA-ST, solid content concentration 30%, primary particle size 10 to 15 nm, manufactured by Nissan Chemical Co., Ltd.)

[0263] B-2: Alcohol dispersion of zinc oxide (ZNTANB 15 WT%-E34, solid content concentration 15%, primary particle size 10 to 15 nm, manufactured by CIK NanoTek Corporation)

[0264] <(C) Ultraviolet light absorber>

[0265] C-1: 2-[2-Hydroxy-4-(1-octyloxycarbonylethoxy)phenyl]-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF Japan Ltd.)

[0266] C-2: 2,4-dihydroxybenzophenone (Seesorb 106, manufactured by Shipro Kasei Kaisha, Ltd.)

[0267] <(D) Hindered amine light stabilizer>

[0268] D-1: Neutral hindered amine light stabilizer (TINUVIN 249, manufactured by BASF Japan Ltd.)

[0269] <(E) Solvent>

[0270] E-1: Propylene glycol monomethyl ether

[0271] <(F) Dehydrating agent>

[0272] F-1: Ethyl orthoformate

[0273] <(G) Leveling agent>

[0274] G-1: LE-604 (manufactured by Kyoeisha Chemical Co., Ltd.)

[0275] [5]Manufacture of coated articles

[0276] [Examples 1 to 8, Comparative Examples 1 to 4]

[0277] Each primer composition obtained in the above-mentioned preparation example and comparative preparation example was applied by dip coating on a polycarbonate resin plate (5 mm thick, product name: Takiron PC Clear-1600, manufactured by Takiron Co., Ltd.) whose surface had been cleaned to form a 5-10 μm cured film, and then heated and cured at 130° C. for 90 minutes to form a primer layer.

[0278] After the obtained test piece was left to cool to room temperature, the silicone composition described in Table 2 and Table 3 (HC-1 or HC-2 prepared in Synthesis Example 4 or Comparative Synthesis Example 1) was applied on the primer layer by dip coating to form a cured film of 5 μm or more and less than 10 μm, and then cured at 120°C for 60 minutes to form a siloxane-based hard coating.

[0279] Next, the surface of the silicone hard coating was irradiated with light using a Xe2 excimer lamp with a wavelength of 172 nm in a N2 atmosphere so that the light irradiation amount was 2 J / cm 2 , a photomodification layer with a film thickness of 0.1 to 0.4 μm was produced.

[0280] [Comparative Example 5]

[0281] A test piece of Comparative Example 5 was obtained in the same manner as in Examples 1 to 8 and Comparative Examples 1 to 4 except that the coating was performed by dip coating so that the film thickness of the primer layer was 22 μm and the film thickness of the hard coat layer was 16 μm.

[0282] [Comparative Example 6]

[0283] A test piece of Comparative Example 6 was obtained in the same manner as in Examples 1 to 8 and Comparative Examples 1 to 4 except that the light-modifying layer was not formed.

[0284] [6] Evaluation of the physical properties of coated articles

[0285] The coated articles obtained in the above-mentioned Examples and Comparative Examples were used as test pieces, and various physical properties were evaluated. The results are shown in Tables 2 and 3.

[0286] (1) Surface hardness of the film:

[0287] The hardness of the film in the present invention is determined by a nanoindentation method using a nanoindenter (ENT-NEXUS, manufactured by Elionix, Inc.).

[0288] Specifically, the resin substrate having a silicone hard coating on the outermost surface prepared in the above-mentioned embodiments and comparative examples was cut into pieces of 15 mm × 15 mm, an instant adhesive (Aron Alpha fast-acting multipurpose, manufactured by Toagosei Co., Ltd.) was applied to a special sample fixing substrate (10 mm × 10 mm, thickness 1 mm), and the substrate side of the above-mentioned sample was bonded to the above-mentioned fixing substrate to obtain a measurement sample.

[0289] The obtained measurement sample was fixed on a dedicated sample fixing table so that the silicone hard coating side was in contact with the indenter. The Berkovich-type indenter was pressed into the film surface at room temperature (23°C). The data obtained when the indentation load reached 0.5 mN were analyzed using dedicated software to determine the surface hardness of the film.

[0290] The same operation was performed on three different points in each sample to determine the surface hardness, and the average value was calculated.

[0291] (2) Initial appearance of the membrane:

[0292] The film appearance of the test piece was visually observed.

[0293] (3) Transparency:

[0294] The haze of the film was measured using a haze meter (NDH2000, manufactured by Nippon Denshoku Industries, Ltd.).

[0295] (4) One-time tightness:

[0296] According to JIS K5400, a razor blade is used to form 6 cuts in the vertical and horizontal directions at 2 mm intervals in the test piece to make 25 checkerboards. After the commercially available transparent tape is well adhered, it is peeled off sharply in the 90° forward direction. The number of grids (X) remaining without peeling off the film is represented by X / 25.

[0297] (5) Water resistance and water tightness:

[0298] After the test piece was immersed in boiling water for 2 hours, an adhesion test was performed in the same manner as in the above (4).

[0299] (6) Scratch resistance:

[0300] According to ASTM1044, the wear wheel CS-10F was installed in the Taper wear tester, and the haze after 1000 revolutions under a load of 500 gf was measured. The scratch resistance ΔHz (%) is expressed as (haze after test (%)) - (haze before test (%)).

[0301] (7) Heat resistance:

[0302] The test piece was placed in an oven at 110° C., and the appearance of the film after 1000 hours was observed and evaluated according to the following criteria.

[0303] ○: No abnormality

[0304] ×: There are cracks in the film

[0305] (8) Weather resistance: SUV promoted weather resistance test:

[0306] Weather resistance was evaluated under the same conditions as those described in International Publication No. 2020 / 066993. That is, a Super UV Tester (SUV) manufactured by Iwasaki Electric Co., Ltd. was used to irradiate for 4 hours (irradiation intensity 90 mW / cm 2 , blackboard temperature 63°C, humidity 70%), 4 hours of darkness (blackboard temperature 63°C, humidity 90%), and 4 hours of condensation (blackboard temperature 30°C, humidity 95%) are taken as one cycle. Confirm the presence or absence of film cracks and film peeling after 600 hours (50 cycles) of the test, and evaluate according to the following standards.

[0307] [Weather-resistant film cracks]

[0308] The film appearance after the weather resistance test was evaluated according to the following criteria.

[0309] ○: No abnormality

[0310] ×: Cracked

[0311] [Weather-resistant film peeling]

[0312] The state of the film after the weather resistance test was evaluated according to the following criteria.

[0313] ○: No abnormality

[0314] ×: Peel off

[0315] [Table 2]

[0316]

[0317] [Table 3]

[0318]

[0319] *Cannot be confirmed due to membrane peeling

[0320] As shown in Table 2, in the coated articles of Examples 1 to 8 that satisfy the essential features of the present invention, the transparency of the coating and the adhesion to the polycarbonate resin substrate are good, and the scratch resistance ΔHz is 2 points or less, showing excellent scratch resistance. In addition, it can be seen that there is no cracking or peeling of the coating after the heat resistance test and the SUV weather resistance test, and it has excellent heat resistance and weather resistance.

[0321] On the other hand, as shown in Table 3, when a vinyl copolymer without an alkoxysilyl group was used as in Comparative Examples 1 and 2, cracks were generated after the heat resistance test, and peeling of the film occurred after the SUV weather resistance test. This indicates that the vinyl copolymer having an alkoxysilyl group has the effect of improving the heat resistance and weather resistance of the coated article including the light-modifying layer.

[0322] In addition, even when a vinyl copolymer having an alkoxysilyl group is used as in Comparative Example 3, when no ultraviolet absorber is included in the hard coat layer, although the heat resistance is good, the scratch resistance is deteriorated, and peeling of the film occurs after the SUV weather resistance test. This is believed to be because, since no ultraviolet absorber is included in the hard coat layer, the irradiation light during the photomodification reaches the primer layer, deteriorating the primer layer, thereby deteriorating the adhesion of the film.

[0323] When a large amount of inorganic particles were introduced as in Comparative Example 4 or the film thickness was too thick as in Comparative Example 5, the balance between the thermal expansion and stress relaxation properties of the primer layer was lost, the adhesion deteriorated, and cracks occurred early in the heat resistance test and the weather resistance test.

[0324] In addition, when a vinyl copolymer having an alkoxysilyl group is used in the primer component and a silicone hard coat layer containing a UV absorber is laminated as in Comparative Example 6, although the heat resistance and SUV weather resistance become good, the scratch resistance does not become good because there is no light modification layer.

[0325] From the above results, it is understood that the coated articles of Examples 1 to 8, which satisfy the essential characteristics of the present invention, have excellent transparency, scratch resistance, heat resistance, and weather resistance of the coating.

Claims

1. A coated article comprising a resin substrate, a primer layer provided on the resin substrate, a hard coating layer provided on the primer layer, and a light-modifying layer formed on the surface layer of the hard coating layer, The primer layer is a cured film of a primer composition comprising (A) 100 parts by mass of a vinyl (co)polymer and (B) 1 to 19 parts by mass of inorganic particles having a median diameter of 1 to 100 nm as measured by a dynamic light scattering method. The (A) vinyl (co)polymer comprises (A-1) a vinyl (co)polymer having an alkoxysilyl group, the thickness of the primer layer is 1 to 20 μm, The hard coating layer is a cured film of a silicone composition comprising (a) a silicone resin obtained by (co)hydrolyzing and condensing at least one selected from the group consisting of alkoxysilane represented by the following formula (1) and its (partial) hydrolysis-condensation product, (b) colloidal silica, and (c) an ultraviolet absorber, wherein the film thickness of the hard coating layer is 1 to 15 μm. R 1 m Si(OR 2 ) 4-m (1) In the formula, R 1 Each independently represents a hydrogen atom, or a substituted or unsubstituted monovalent hydrocarbon group, and multiple R 1 can be bonded to each other to form a linking group, R 2 Each independently represents an alkyl group having 1 to 3 carbon atoms, and m is 0, 1 or 2.

2. The coated article according to claim 1, wherein The light-modifying layer comprises silicon dioxide.

3. The coated article according to claim 1 or 2, wherein: The (c) ultraviolet absorber includes a reactive ultraviolet absorber represented by the following general formula (2) and a (partial) hydrolysis condensate thereof, [Chemistry 1] In the formula, R 3 are each independently a hydrogen atom, a hydroxyl group, an alkyl group having 1 to 5 carbon atoms, or a group represented by the following general formula (3), R 3 At least one of them is a group represented by the following general formula (3), *-O-(CH2) j -SiR 4 k (OR 5 ) 3-k (3) In the formula, R 4 and R 5 Each independently represents an alkyl group having 1 to 5 carbon atoms, j represents an integer of 1 to 8, k represents an integer of 0 to 2, and an asterisk * represents a bond to an adjacent atom.

4. The coated article according to any one of claims 1 to 3, wherein The surface hardness of the hard coating layer measured by nanoindentation method is 0.10 to 0.50 GPa.

5. The coated article according to any one of claims 1 to 4, wherein (B) The inorganic particles include particles of one or more selected from the group consisting of silicon dioxide, zinc oxide, titanium oxide, and cerium oxide.

6. The coated article according to any one of claims 1 to 5, wherein The primer composition includes (A-1) a vinyl copolymer having an alkoxysilyl group and an ultraviolet absorbing group.

7. The coated article according to any one of claims 1 to 6, wherein The primer composition further comprises (C) one or more ultraviolet absorbers selected from triazine derivatives and benzophenone derivatives.

8. The coated article according to any one of claims 1 to 7, wherein The primer composition further comprises (D) a hindered amine light stabilizer.

9. The coated article according to any one of claims 1 to 8, wherein The film thickness of the primer layer is 3 to 15 μm, and the film thickness of the hard coating layer is 3 to 13 μm.

10. A method for producing a coated article according to any one of claims 1 to 9, comprising the step of irradiating the surface of the hard coating layer with light having a wavelength of 300 nm or less to form a light-modified layer on the surface layer of the hard coating layer.

Citation Information

Patent Citations

  • Manufacture of silicon carbide heating body

    JP1986056187B2

  • Resin window member for vehicle and resin composite module for vehicle

    WO2020044705A1

  • Primer composition and coated article

    CN101469249A

  • Plastic article for automotive glazing

    CN102529248A

  • Resin substrate provided with hard-coat coating, and method for producing same

    CN103328210A